Proceedings of the 2nd International Conference on Experimental and Computational Mechanics in Engineering ICECME 2020, Banda Aceh, October 13–14 - Tanda, Maria Giovanna; Chiapponi, Luca (Lecture Notes in Mechanical Engineering, 2021)
This book gathers a selection of peer-reviewed papers presented at the 2nd International Conference on Experimental and Computational Mechanics in Engineering (ICECME 2020), held as a virtual conference and organized by Universitas Syiah Kuala, Banda Aceh, Indonesia, on 13–14 October 2020. The contributions, prepared by international scientists and engineers, cover the latest advances in computational mechanics, metallurgy and material science, energy systems, manufacturing processing systems, industrial and system engineering, biomechanics, artificial intelligence, micro/nano-engineering, micro-electro-mechanical system, machine learning, mechatronics, and engineering design. The book is intended for academics, including graduate students and researchers, as well as industrial practitioners working in the areas of experimental and computational mechanics.